Development of Learning Tools Based on a Realistic Mathematics Approach with the Karo Cultural Context to Improve Student’s Mathematical Connection Ability in Class XII - Atania Christianti Br Ginting; Nur Indah Simamora (Proceeding International Conference on Religion, Science and Education, 2023)
The purposes of the research were to 1) Produce valid, practical and effective quality learning tools, which were developed based on a realistic mathematical approach with the Karo Cultural Context (RME-KCC) for class XII of SMA Masehi Berastagi; 2) Analyzing the increase in students' mathematical connection abilities using learning tools based (RME-KCC). This research is a development research using the EDDIE development model. Learning tools produced from this study are Learning Implementation Plans, Student Books, Student Worksheets, Student’s Mathematical Connection Ability Tests. Based on the research results obtained 1) Learning tools based on RME-KCC have met the valid, practical, and effective criteria in terms of each criterion; 2) There is an increase in students' mathematical connection abilities by using learning tools based on RME-KCC seen from the N-gain value in trial I of 0.32 (criterion "moderate") increased to 0.56 (criteria "moderate") in the trial II.